2012
DOI: 10.1007/s11274-011-1001-2
|View full text |Cite
|
Sign up to set email alerts
|

Richness of endophytic fungi isolated from Opuntia ficus-indica Mill. (Cactaceae) and preliminary screening for enzyme production

Abstract: Opuntia ficus-indica Mill. (forage cactus) is farmed with relative success in the semi-arid region of the Brazilian northeast for commercial purposes, particularly as forage and food. Endophytic microorganisms are those that can be isolated inside plant tissues and can be a new source to production of enzymes with different potentialities. The objective of this study was to describe the richness of endophytic fungi from O. ficus-indica and to detect the capacity of these species to produce extracellular hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 56 publications
6
68
1
Order By: Relevance
“…Endophytic fungi are important producers of enzymes, and have high capability for production of extracellular enzymes such as cellulases, chitinases, laccase, pectinases, xylanases, proteases, amylases, β-galactosidase and other catabolic enzymes (Jordaan et al 2006;Bischoff et al 2009;Borges et al 2009;Rajulu et al 2011;Bezerra et al 2012). Chitinase is applied to the biological control of phytopathogens as it degrades the chitin of the pathogen cell wall.…”
Section: Enzyme Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endophytic fungi are important producers of enzymes, and have high capability for production of extracellular enzymes such as cellulases, chitinases, laccase, pectinases, xylanases, proteases, amylases, β-galactosidase and other catabolic enzymes (Jordaan et al 2006;Bischoff et al 2009;Borges et al 2009;Rajulu et al 2011;Bezerra et al 2012). Chitinase is applied to the biological control of phytopathogens as it degrades the chitin of the pathogen cell wall.…”
Section: Enzyme Productionmentioning
confidence: 99%
“…Recent studies have revealed a large richness of endophytic fungal species and diverse metabolites with different functions (Zimmerman and Vitousek 2012;Xiao et al 2014;Zhang et al 2014a, b). In some cases, they can enhance plant growth (Waller et al 2005), act as biological control agents (Zhang et al 2014c), and produce enzymes (Bezerra et al 2012). The endophytic fungi are relatively unexplored and could be potential sources of novel natural products for exploitation in medicine, agriculture, and industry (Strobel et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such work has greatly enhanced our understanding of the geographic-, host-, and tissue-affiliations of fungi that are symbiotic with ecologically important plants in semi-arid grasslands and deserts, especially grasses and sedges [34, 47], gypsophilous plants [69], and selected dicotyledonous plants such as Atriplex spp. [16, 54] and some Cactaceae [17, 83; see also 51]. However, gaps remain with regard to understanding the diversity and composition of fungal communities in above-ground tissues of many woody plants in arid ecosystems, including those non-succulent species that form the dominant cover in some of the world's most biotically rich deserts.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it causes severe diseases in a variety of hosts, including plants and vertebrates (Faisal et al, 2007;Tullio et al, 2010). However, few studies have examined the xylanolytic activity on Phoma species (Bradner et al, 1999;Yang et al, 2005;Bezerra et al, 2012).…”
Section: Discussionmentioning
confidence: 99%